First Christmas on Huckleberry Hill - Beckstrand, Jennifer (Beckstrand, Jennifer. Matchmakers of Huckleberry Hill., 2021)
During this holiday season, Anna Yoder can't help hoping that she and her old schoolmate Felty Helmuth, who is being ostracized by their Amish community for his Korean War army service, can find a way to be the perfect match.